Study of Electrical Properties of Poly (Vinyl Alcohol)/ Alumina (PVA/Al2O3)Nanocomposites (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In the present work, nanocomposites of polyvinyl alcohol and alumina nanoparticles, have been prepared by casting technique. The alumina nanoparticles were added to polyvinyl alcohol with different concentrations are(0, 4, 8, 12 and16) wt.% .The electrical properties of nanocomposites were studied. The experimental results showed that the D.C electrical conductivity increases with increase the alumina nanoparticles concentrations and temperature. The activation energy of D.C electrical conductivity decreases with increase of alumina nanoparticle concentrations," and by find the samples by the microscopic photographs.